2017
DOI: 10.1016/j.ajog.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain

Abstract: Prenatal care providers are advised to evaluate maternal weight at each regularly scheduled prenatal visit, monitor progress toward meeting weight gain goals, and provide individualized counseling if significant deviations from a woman’s goals occur. Today, nearly 50% of women exceed their weight gain goals with overweight and obese women having the highest prevalence of excessive weight gain. Risks of inadequate weight gain include low birth weight and failure to initiate breastfeeding whereas the risks of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
276
1
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(301 citation statements)
references
References 71 publications
7
276
1
17
Order By: Relevance
“…In our study, maternal body size early in pregnancy was negatively associated with gestational weight gain, which is in line with epidemiological studies . The inverse association between body size and weight gain is postulated to reflect a biological adaptation of women with increased adiposity to minimize the risk for pregnancy complications and infant outcomes . The present study is the first to use gold‐standard methodologies, i.e., air displacement plethysmography combined with stable isotope dilution, and to show that differences in weight gain during pregnancy in women with obesity are largely due to differences in fat accumulation.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, maternal body size early in pregnancy was negatively associated with gestational weight gain, which is in line with epidemiological studies . The inverse association between body size and weight gain is postulated to reflect a biological adaptation of women with increased adiposity to minimize the risk for pregnancy complications and infant outcomes . The present study is the first to use gold‐standard methodologies, i.e., air displacement plethysmography combined with stable isotope dilution, and to show that differences in weight gain during pregnancy in women with obesity are largely due to differences in fat accumulation.…”
Section: Discussionsupporting
confidence: 89%
“…More women today are entering pregnancy with an elevated body mass index (BMI). As obesity is more prevalent, the incidence of complications associated with obesity during pregnancy, such as increased rates of hypertensive disorders of pregnancy, fetal macrosomia, and cesarean birth rates, is increasing . The 2011 to 2012 National Health and Nutrition Examination Survey found that the prevalence of obesity in women of reproductive age (20‐39 years) in the United States is 31.8% .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of obesity and macrosomia significantly increases the chance of cesarean delivery [6]. Both pre-pregnancy BMI category and gestational weight gain are independent contributors to the development of a large for gestational age or macrosomic infant [7][8]. Obese women tend to have higher gestational weight gain, despite stricter weight gain recommendations, and hence larger birth weight babies [7].…”
Section: Factors Contributing To Cesarean Delivery In Obese Womenmentioning
confidence: 99%
“…Both pre-pregnancy BMI category and gestational weight gain are independent contributors to the development of a large for gestational age or macrosomic infant [7][8]. Obese women tend to have higher gestational weight gain, despite stricter weight gain recommendations, and hence larger birth weight babies [7]. A large fetus, for obvious reasons, predisposes the mother to a protracted labor course and cephalopelvic disproportion leading to an indicated cesarean delivery.…”
Section: Factors Contributing To Cesarean Delivery In Obese Womenmentioning
confidence: 99%